Gender and local floodplain management institutions: a case study from Bangladesh - Sultana, Parvin; Thompson, Paul (International Food Policy Research Institute, 2006)
Floodplain wetlands are the major common pool natural resource in Bangladesh. Mostly men fish, and both men and women collect aquatic plants and snails. Case studies contrast a women-only, men-only, and mixed community based organization (CBO), each of which manages a seasonal floodplain wetland. The two CBOs in which women hold key positions are in Hindu communities where more women use aquatic resources, work for an income, and belong to other local institutions. In the oldest of these CBOs, more women have gradually become office bearers as their recognition in the community has grown. In the Muslim community, only a few women collect aquatic resources and in this community most women do not perceive floodplain natural resource constraints to be very important to them. These women have no role in the CBO and feel that they have no say in decisions about the fishery, unlike many women in the other two sites. The fishery management activities in all three sites are similar and catches and biodiversity appear to have improved, demonstrating that women can play an effective role in community organizations for fishery management. Those who are represented in the CBOs reported significant increases in their participation and influence. Men and women in all three sites recognized that decisionmaking and management of their fisheries had improved, but community support and compliance were higher where both men and women had an active role in this process. Women had a more diverse set of criteria for effective CBOs than men. The men-only CBO saw itself as more of a membership based organization than as representing all of the community.